Gender Diversity Programs, Perceived Potential for Advancement, and Organizational Attractiveness: An Empirical Examination of Women in the United States and France. (June 2016) - Olsen, Jesse E.; Parsons, Charles K.; Martins, Luis L.; Ivanaj, Vera
We conducted an experimental study to compare the effects of organization-sponsored gender diversity management programs on women's evaluations of organizational attractiveness in two countries: the United States and France. Importantly, we examined perceived potential for advancement as a mediator of the relationship, thus elaborating on an underlying mechanism implied by signaling theory. Results from a sample of 230 women in the United States and France provided overall support for the model. We found that country and individual characteristics affect how diversity management signals are translated into perceptions of the organization. We discuss the theoretical and practical contributions of the study, as well as limitations and opportunities for future research.